P226 Temporal trends in cardiopulmonary exercise testing (CPET) service utilisation. (December 2018) - Thomas, MO; Webber, S; Moore, VC; Mukherjee, R
Abstract : Introduction: CPET is used as a preoperative screening tool to assess fitness; as a disease monitoring tool to determine functional limitation and treatment response; or as a diagnostic tool to identify the cause of breathlessness or exercise intolerance. A previous audit had identified that the service at Birmingham Heartlands Hospital was underutilised for diagnostic purposes. Methods: We conducted a retrospective analysis of CPET referrals between 01/07/2017 and 31/05/2018, and compared with those of 01/07/2013 to 31/05/2014. The source of referral and clinical indication were recorded and presented. Results: Total referrals for CPET were 307 in 2017–2018 compared to 178 in 2013–2014 (see figure 1) indicating a 72.5% increase. The majority of referrals were for surgical disciplines rather than medical disciplines in both time periods (253 vs 54 in 2017–2018; 150 vs 28 in 2013–2014); the proportion of tests for diagnostic purposes has remained the same (17.5% in 2017–2018 vs 16% in 2013–2014). Vascular surgery was the largest source of referrals in both time periods (46.3% in 2017–2018; 61% in 2013–2014). CPET referrals from thoracic surgery and gastrointestinal (upper GI and colorectal) surgery have increased proportionally (9.4% and 17.5% respectively in 2017–2018; 2.2% and 5.6% in 2013–2014). Discussion: CPET offers a unique assessment tool for the investigation of patients with unexplained dyspnoea and can pre-empt invasive, expensive, and potentially unnecessary assessment without definitive diagnosis (Thing et al. Thorax 2011;66 (4):A144). The CPET service has experienced large increase in the number of referrals since 2013. Vascular surgery remains the primary source of referral, but the service has seen an increase in referrals from thoracic, upper GI and colorectal surgery. However, there has been no proportional increase in the use of CPET for diagnostic purposes. The service is evidently growing, but more awareness needs to be raised to increase the utilisation of CPET in diagnosing the cause of breathlessness.